2009
DOI: 10.1158/1541-7786.mcr-09-0069
|View full text |Cite
|
Sign up to set email alerts
|

The Alkylphospholipid Perifosine Induces Apoptosis and p21-Mediated Cell Cycle Arrest in Medulloblastoma

Abstract: Medulloblastoma is the most common malignant cancer of the central nervous system in children. AKT kinases are part of a survival pathway that has been found to be significantly elevated in medulloblastoma. This pathway is a point of convergence for many growth factors and controls cellular processes that are critical for tumor cell survival and proliferation. The alkyl-phospholipid perifosine [octadecyl-(1,1-dimethyl-4-piperidylio) phosphate] is a small molecule inhibitor in clinical trials in peripheral canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Nevertheless, despite not achieving the primary objectives related to significant increases in progression-free survival rates, some optimism still remained for this agent in advanced soft tissue sarcoma patients (Bailey, et al, 2006), as well as to warrant further evaluation of perifosine in combination with rituximab or other active agents in patients with relapsed/refractory Waldenstrom's macroglobulinemia (Ghobrial, et al, 2010), and with currently available therapies in renal cancer (Cho, et al, 2012). Furthermore, a number of studies have reported the potentiation of antitumor activity following combination of perifosine with distinct anticancer drugs in cancer cells derived from several types of leukemia (Nyakern, et al, 2006;Papa, et al, 2008;Tazzari, et al, 2008), multiple myeloma Hideshima, et al, 2006), osteosarcoma (Yao, et al, 2013), medulloblastoma (Kumar, et al, 2009), lung cancer (Elrod, et al, 2007), colon cancer (M. B. Chen, et al, 2012, and glioma (Momota, et al, 2005), as well as following combination of miltefosine with different anticancer compounds or treatments in distinct cancer cell types (Haberkorn, et al, 1992;Papagiannaros, et al, 2006;Spruss, et al, 1993;Thakur, et al, 2013). Thus, phase II clinical trials were conducted with…”
Section: Alkylphosphocholinesmentioning
confidence: 99%
“…Nevertheless, despite not achieving the primary objectives related to significant increases in progression-free survival rates, some optimism still remained for this agent in advanced soft tissue sarcoma patients (Bailey, et al, 2006), as well as to warrant further evaluation of perifosine in combination with rituximab or other active agents in patients with relapsed/refractory Waldenstrom's macroglobulinemia (Ghobrial, et al, 2010), and with currently available therapies in renal cancer (Cho, et al, 2012). Furthermore, a number of studies have reported the potentiation of antitumor activity following combination of perifosine with distinct anticancer drugs in cancer cells derived from several types of leukemia (Nyakern, et al, 2006;Papa, et al, 2008;Tazzari, et al, 2008), multiple myeloma Hideshima, et al, 2006), osteosarcoma (Yao, et al, 2013), medulloblastoma (Kumar, et al, 2009), lung cancer (Elrod, et al, 2007), colon cancer (M. B. Chen, et al, 2012, and glioma (Momota, et al, 2005), as well as following combination of miltefosine with different anticancer compounds or treatments in distinct cancer cell types (Haberkorn, et al, 1992;Papagiannaros, et al, 2006;Spruss, et al, 1993;Thakur, et al, 2013). Thus, phase II clinical trials were conducted with…”
Section: Alkylphosphocholinesmentioning
confidence: 99%
“…[86] Its inhibition by KP-372-1, KP-372-2, A-443654, or perifosine, was reported to inhibit cell growth and induce radio-sensitizing effects in GBM and MB. [87][88][89] Clinical trials of perifosine in GBM patients are ongoing. [90] PTEN is a tumor suppressor usually mutated and inactivated in GBM, with an inverse correlation between its expression and glioma grade.…”
Section: Emt Cell Invasion and Motilitymentioning
confidence: 99%
“…Mechanistically, Perifosine exhibits antitumor activity by preventing Akt translocation to the cell membrane [114] . The drug has demonstrated antitumor effects in neuroblastoma, ovarian cancer, Waldenstrom's macroglobulinemia, medulloblastoma, kidney cancer, endometrial cancer, prostate cancer, myelogenous leukemia, multiple myeloma, squamous cell carcinoma, breast cancer, sarcoma, lung cancer, hepatocellular carcinoma, and other solid tumors [115][116][117][118][119][120][121][122][123][124][125][126][127] . With its success in preclinical models, Perifosine reached phase I and II trials for the treatment of only solid tumors, Waldenstrom's macroglobulinemia, and sarcoma [127][128][129] .…”
Section: Akt Inhibitorsmentioning
confidence: 99%